1976
DOI: 10.1136/jcp.29.7.592
|View full text |Cite
|
Sign up to set email alerts
|

Immunological phenomena in the jejunum and serum after reintroduction of dietary gluten in children with treated coeliac disease.

Abstract: Jejunal mucosal immunoglobulin-containing cells of all three major classes (IgA, IgM, IgG) were increased in coeliac children on gluten-containing diets but only IgM cell numbers were raised in those on gluten-free diets. Patients with subtotal villous atrophy had greater numbers of immunoglobulin-containing cells than patients with normal mucosa. In previously treated patients studied before and after three months on a gluten-containing diet ther was an increase in all three classes of cell, IgM containing ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…Changes in Ig-cell populations were shown to persist longer than histological damage in CD. This finding is consistent with some earlier studies [16,17], though it contradicts other reports [12,35].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Changes in Ig-cell populations were shown to persist longer than histological damage in CD. This finding is consistent with some earlier studies [16,17], though it contradicts other reports [12,35].…”
Section: Discussionsupporting
confidence: 78%
“…There are different relative proportions of IgA-, IgM-, and IgG-containing cells reported to take part in the subepithelial infiltrate, in CD [3,7,12,17,34,35,37] and in CMPI [12,20,33,36]. A consistent difference between CD and CMPI was not demonstrated until this study, based on the evaluation of defined mucosal tissue units and on double-stain immunofluorescent histology suitable for quantitative work [2].…”
Section: Discussionmentioning
confidence: 94%
“…After gluten challenge, deposition of immunoglobulins and C 3 have been observed in the basement membrane and lamina propria of the small bowel in treated adult coeliac patients [5,18]. An increase of IgA-and IgM-containing cells in the mucosa after gluten challenge has been demonstrated by Lancaster-Smith et al [9]. In vitro studies with coeliac jejunal mucosa have shown an increased synthesis of IgA and IgM after challenge with gluten [10], much of this being antibody against gluten [7].…”
Section: Introductionmentioning
confidence: 94%
“…Such findings differed considerably from those in healthy individuals. [46][47][48][49][50][51] It was also found that during a gluten-free diet, the antibody deposits disappeared, but when gluten was reintroduced in the diet of celiac disease patients, the antibody deposition rapidly reappeared. 49,52,53 After the identification of TG2 as the celiac disease autoantigen, 36 it was demonstrated that the patient autoantibodies also target the autoantigen TG2 in tissues.…”
Section: Intestinal Autoantibodiesmentioning
confidence: 99%
“…45 Immediately thereafter, similar IgA deposits in the basement membrane area were reported in the small-bowel mucosa of untreated celiac patients in conjunction with increases in the number of immunoglobulin-containing cells. [46][47][48][49] Immunoelectron microscopic studies revealed heavy deposits of IgA in the basement membrane of surface epithelial cells, in crypt epithelium, around the subepithelial fibroblasts and in the walls of blood vessels in the intestinal mucosa of Antibodies in celiac disease S Caja et al 104 celiac patients. Such findings differed considerably from those in healthy individuals.…”
Section: Intestinal Autoantibodiesmentioning
confidence: 99%